Blue light absorption type composite rare earth coating material and preparation method thereof
By using high-energy ball mills and high-pressure molding machines to process inorganic oxide powders in anti-blue light products, and forming dense blue light absorption coating materials in vacuum sintering furnaces, the problem of reflecting blue light in existing products is solved and higher blue light is achieved Absorption effect and better user experience.
Patent Information
- Application Number
- CN202411399487.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-09
AI Technical Summary
Existing anti-blue light products form a reflective film layer through vacuum coating, resulting in the reflection of dazzling blue light under high light intensity, affecting the user experience.
A high-energy ball mill is used to mix micron-scale inorganic oxide powder, granulated through a high-pressure molding machine and sintered in a vacuum sintering furnace to form a dense blue light absorption coating material, and a blue light absorption nano film is formed on the surface of the substrate using vacuum coating technology.
It realizes the absorption rather than reflection of blue light, reduces the reflectivity of the product, and improves the comfort and experience of use.
Smart Images

Figure CN119287318A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of vacuum optical coating, and specifically relates to a blue light absorbing composite rare earth coating material and a preparation method thereof. Background Art
[0002] Long-term exposure to blue light can easily cause damage to the eyes, especially causing lesions in the macula. Blue light can penetrate the lens to reach the retina, causing certain damage to the retina, thereby accelerating the oxidation of eye cells, producing a large number of free radicals, and leading to macular degeneration; blue light can cause blurred vision and visual fatigue; blue light can inhibit the secretion of melatonin, affect sleep, and increase the probability of major diseases. The survey found that most of the current anti-blue light mobile phone tempered films, anti-blue light glasses and other products use different refractive indices of coating materials for optical design, and form a blue light reflective film layer on the substrate surface through vacuum coating to achieve the effect of anti-blue light.
[0003] However, this method has the defect of high reflection. When the light intensity is high, the surface of the product will reflect glaring blue light, seriously affecting the user experience. Summary of the invention
[0004] The purpose of the present invention is to provide a blue light absorbing composite rare earth coating material and a preparation method thereof in order to solve the above-mentioned problems.
[0005] The technical solution adopted by the present invention is as follows: a blue light absorbing composite rare earth coating material and a preparation method thereof, which comprises the following steps:
[0006] S1: Using a high-energy ball mill, different proportions of micron-sized silicon monoxide, lanthanum titanate, holmium oxide, praseodymium oxide, lutetium oxide, cerium oxide and other inorganic oxide powder raw materials are mixed uniformly;
[0007] The ratio is:
[0008] 50.36 parts by weight of silicon monoxide, 30.95 g of lanthanum titanate, 28.55 to 108.55 parts by weight of holmium oxide, 10.37 to 30.37 parts by weight of praseodymium oxide, 9.58 to 49.58 parts by weight of lutetium oxide, and 20.19 to 80.19 parts by weight of cerium oxide;
[0009] S2: Using a high pressure molding machine to mold and granulate the mixed material to obtain a granular material with a particle size range of 3-5 mm;
[0010] S3: placing the granular material in a vacuum sintering furnace and sintering it for 4 hours at a vacuum degree of 1.0×10-2Pa and a temperature of 1400°C to fully react and further improve the density of the granular material;
[0011] S4: vacuum-seal the sintered coating material for future use;
[0012] S5: placing the eyeglass substrate on a special fixture, and performing ultrasonic cleaning using a cleaning machine and deionized water respectively; and drying the cleaned substrate using a blower dryer at a temperature of 50°C;
[0013] S6: placing the dried substrate on the umbrella stand of the vacuum coating machine and fixing it with a special clamp, and adding the sintered blue light absorbing coating material and silica particles into the crucible;
[0014] S7: close the hatch, set the deposition rate and film thickness of the coating material and other parameters, and run the vacuum coating machine to perform the vacuum coating process;
[0015] S8: After the coating is completed, use a spectrophotometer and a reflectometer to test the product's light transmittance, reflectivity and other performance to verify the product's blue light absorption performance, and the entire blue light absorption type composite rare earth coating material and its preparation process are completed.
[0016] In a preferred embodiment, in step S1, the speed of the ball mill should be controlled at 300-500 rpm, and the ball milling time should be set to 2-4 hours to ensure that the powder raw materials are mixed evenly. At the same time, the ball mill should be filled with zirconium oxide balls with a diameter of 3-10 mm, and the ball-to-material ratio is 10:1 to enhance the mixing effect.
[0017] In a preferred embodiment, in step S2, the molding pressure should be controlled at 30-50 MPa, and the holding time should be 5-10 minutes. During the granulation process, the particle size distribution of the particles should be as uniform as possible to ensure that the particle size of the granular material is within the range of 3-5 mm.
[0018] In a preferred embodiment, in step S3, the vacuum degree should be maintained at 1.0×10^-2Pa, the sintering temperature is 1400°C, the heating rate is controlled at 5-10°C / min, and the holding time is 4 hours. During the sintering process, the temperature should be evenly distributed to avoid cracks inside the material.
[0019] In a preferred embodiment, in step S4, when the vacuum seal is used for storage, a vacuum packaging bag with good sealing performance should be used, and the material should be stored at room temperature, in a dry, light-proof environment to prevent the coating material from being damp and oxidized.
[0020] In a preferred embodiment, in step S5, during ultrasonic cleaning, the temperature of the cleaning solution is controlled at 40-60°C, the ultrasonic frequency is 40kHz, and the cleaning time is 10-15 minutes. The resistivity of deionized water should be greater than 10MΩ·cm to ensure the cleanliness of the substrate surface.
[0021] In a preferred embodiment, in step S6, when the substrate on the umbrella stand of the vacuum coating machine is fixed, the distance between the substrate and the coating material should be controlled to be 80-120 mm. The materials in the crucible should be fully mixed to ensure uniform coating.
[0022] In a preferred embodiment, in step S7, during the vacuum coating process, the deposition rate of the coating material is set to 0.1-0.5 nm / s, and the film thickness is controlled to 50-200 nm according to actual needs. The vacuum degree of the vacuum coating machine should be maintained below 1.0×10^-3Pa.
[0023] In a preferred embodiment, in step S8, when testing the light transmittance and reflectance, the wavelength range of the spectrophotometer should be set to 380-780nm, and the detection angles of the reflectometer should be 0°, 45°, and 90°. The blue light absorption performance of the product can be evaluated through the test data.
[0024] In a preferred embodiment, in step S8, after the performance test is completed, if the product is qualified, it is packaged, labeled and put into storage. During the packaging process, it should be ensured that there are no scratches or stains on the surface of the product, and anti-static and moisture-proof packaging materials should be used. At the same time, the product is batch labeled for easy traceability and management.
[0025] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0026] In the present invention, high-purity micron-grade inorganic raw material powders of different components are mixed evenly by a high-energy ball mill, and then the mixture is granulated by a high-pressure molding machine, and finally the granular material is placed in a vacuum sintering furnace for high-temperature sintering. Under high temperature and oxygen-deficient conditions, oxygen loss and oxygen-snatching reactions occur between the component materials, and finally a dense granular blue light absorbing coating material is formed by sintering. A blue light absorbing nano film is formed on the surface of a resin or glass substrate by vacuum coating. The blue light absorbing coating material can adjust the blue light absorption ratio by regulating the proportion of components to meet the needs of different products and different application scenarios, and the product has a low reflectivity, is soft and not dazzling, thereby improving the comfort and experience during use. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram of the process principle of the present invention. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0029] Reference Figure 1 ,
[0030] A blue light absorbing composite rare earth coating material and a preparation method thereof, comprising the following steps:
[0031] S1: Using a high-energy ball mill, different proportions of micron-sized silicon monoxide, lanthanum titanate, holmium oxide, praseodymium oxide, lutetium oxide, cerium oxide and other inorganic oxide powder raw materials are mixed uniformly;
[0032] The ratio is:
[0033] 50.36 parts by weight of silicon monoxide, 30.95 g of lanthanum titanate, 28.55 to 108.55 parts by weight of holmium oxide, 10.37 to 30.37 parts by weight of praseodymium oxide, 9.58 to 49.58 parts by weight of lutetium oxide, and 20.19 to 80.19 parts by weight of cerium oxide;
[0034] S2: Using a high pressure molding machine to mold and granulate the mixed material to obtain a granular material with a particle size range of 3-5 mm;
[0035] S3: placing the granular material in a vacuum sintering furnace and sintering it for 4 hours at a vacuum degree of 1.0×10-2Pa and a temperature of 1400°C to fully react and further improve the density of the granular material;
[0036] S4: vacuum-seal the sintered coating material for future use;
[0037] S5: placing the eyeglass substrate (resin) on a special fixture, and performing ultrasonic cleaning using a cleaning machine and deionized water respectively; and drying the cleaned substrate using a blower dryer at a temperature of 50° C.;
[0038] S6: placing the dried substrate on the umbrella stand of the vacuum coating machine and fixing it with a special clamp, and adding the sintered blue light absorbing coating material and silica particles into the crucible;
[0039] S7: close the hatch, set the deposition rate and film thickness of the coating material and other parameters, and run the vacuum coating machine to perform the vacuum coating process;
[0040] S8: After the coating is completed, use a spectrophotometer and a reflectometer to test the product's light transmittance, reflectivity and other performance to verify the product's blue light absorption performance, and the entire blue light absorption type composite rare earth coating material and its preparation process are completed.
[0041] In step S1, the speed of the ball mill should be controlled at 300-500 rpm, and the ball milling time should be set to 2-4 hours to ensure that the powder raw materials are mixed evenly. At the same time, the ball milling tank should be filled with zirconia balls with a diameter of 3-10 mm, and the ball-to-material ratio should be 10:1 to enhance the mixing effect.
[0042] In step S2, the molding pressure should be controlled at 30-50 MPa, and the holding time should be 5-10 minutes. During the granulation process, the particle size distribution of the particles should be as uniform as possible to ensure that the particle size of the granular material is within the range of 3-5 mm.
[0043] In step S3, the vacuum degree should be maintained at 1.0×10^-2Pa, the sintering temperature is 1400°C, the heating rate is controlled at 5-10°C / min, and the holding time is 4 hours. During the sintering process, the temperature should be evenly distributed to avoid cracks inside the material.
[0044] In step S4, when the vacuum seal is used for storage, a vacuum packaging bag with good sealing performance should be used, and the material should be stored in a dry, light-proof environment at room temperature to prevent the coating material from being damp or oxidized.
[0045] In step S5, during ultrasonic cleaning, the temperature of the cleaning solution is controlled at 40-60°C, the ultrasonic frequency is 40kHz, and the cleaning time is 10-15 minutes. The resistivity of deionized water should be greater than 10MΩ·cm to ensure the cleanliness of the substrate surface.
[0046] In step S6, when the substrate on the umbrella stand of the vacuum coating machine is fixed, the distance between the substrate and the coating material should be controlled at 80-120 mm. The materials in the crucible should be fully mixed to ensure uniform coating.
[0047] In step S7, during the vacuum coating process, the deposition rate of the coating material is set to 0.1-0.5 nm / s, and the film thickness is controlled to 50-200 nm according to actual needs. The vacuum degree of the vacuum coating machine should be maintained below 1.0×10^-3Pa.
[0048] In step S8, when testing the light transmittance and reflectance, the wavelength range of the spectrophotometer should be set to 380-780nm, and the detection angles of the reflectometer should be 0°, 45°, and 90°. The blue light absorption performance of the product can be evaluated through the test data.
[0049] In step S8, after the performance test is completed, if the product is qualified, it will be packaged, labeled and put into storage. During the packaging process, it should be ensured that there are no scratches or stains on the surface of the product, and anti-static and moisture-proof packaging materials should be used. At the same time, the product is batch labeled for easy traceability and management.
[0050] Example 1
[0051] (1) using a high-energy ball mill to uniformly mix 50.36 parts by weight of silicon monoxide, 30.95 parts by weight of lanthanum titanate, 28.55 parts by weight of holmium oxide, 10.37 parts by weight of praseodymium oxide, 9.58 parts by weight of lutetium oxide, 20.19 parts by weight of cerium oxide and other micron-sized inorganic oxide powder raw materials;
[0052] (2) using a high pressure molding machine to mold and granulate the mixed material to obtain a granular material with a particle size ranging from 3 to 5 mm;
[0053] (3) Place the granular material in a vacuum sintering furnace at a vacuum degree of 1.0×10- 2 Pa, sintered at 1400°C for 4 hours to fully react and further improve the density of the pellets;
[0054] (4) vacuum sealing the sintered coating material for future use;
[0055] (5) placing the lens substrate (resin) on a special fixture, and performing ultrasonic cleaning using a cleaning machine and deionized water respectively; and drying the cleaned lens substrate using a blower dryer at a temperature of 50° C.;
[0056] (6) placing the dried substrate on the umbrella stand of the vacuum coating machine and fixing it with a special clamp, and adding the sintered blue light absorbing coating material and silica particles into the crucible;
[0057] (7) Close the hatch, set the deposition rate and film thickness of the coating material and other parameters.
[0058] Run the vacuum coating machine to carry out the vacuum coating process;
[0059] (8) After coating, use a spectrophotometer and a reflectometer to test the product's light transmittance and reflectivity to verify its blue light absorption performance.
[0060] The prepared eyeglass lens product covered with blue light absorbing nano-film is light yellow in color, with an average light transmittance of 85%, a reflectivity of 4%, and a blue light absorption of 25% at a wavelength of 450nm. The product has a good blue light absorption effect, while also solving the problem of high reflectivity, greatly improving the product's performance and user experience to meet the needs of different groups of people.
[0061] Example 2
[0062] (1) using a high-energy ball mill, 50.36 parts by weight of silicon monoxide, 30.95 parts by weight of lanthanum titanate, 68.55 parts by weight of holmium oxide, 20.37 parts by weight of praseodymium oxide, 29.58 parts by weight of lutetium oxide, 50.19 parts by weight of cerium oxide and other micron-sized inorganic oxide powder raw materials were mixed uniformly;
[0063] (2) using a high pressure molding machine to mold and granulate the mixed material to obtain a granular material with a particle size ranging from 3 to 5 mm;
[0064] (3) Place the granular material in a vacuum sintering furnace at a vacuum degree of 1.0×10- 2Pa, sintered at 1400°C for 4 hours to fully react and further improve the density of the pellets;
[0065] (4) vacuum sealing the sintered coating material for future use;
[0066] (5) Place the tempered film substrate (glass) of the mobile phone on a special fixture, and use a cleaning machine and deionized water for ultrasonic cleaning respectively; and use a blower dryer to dry the cleaned substrate at a temperature of 80°C;
[0067] (6) placing the dried substrate on the umbrella stand of the vacuum coating machine and fixing it with a special clamp, and adding the sintered blue light absorbing coating material and silica particles into the crucible;
[0068] (7) Close the hatch, set the deposition rate and film thickness of the coating material and other parameters.
[0069] Run the vacuum coating machine to carry out the vacuum coating process;
[0070] (8) After coating, use a spectrophotometer and a reflectometer to test the product's light transmittance and reflectivity to verify its blue light absorption performance.
[0071] The prepared mobile phone tempered film product covered with blue light absorbing nano-film is light yellow in color, with an average light transmittance of 75%, a reflectivity of 5%, and a blue light absorption of 40% at a wavelength of 450nm. The product has better blue light absorption effect and also solves the problem of high reflectivity, meeting the needs of different groups of people and improving the product's user experience.
[0072] Example 3
[0073] (1) using a high-energy ball mill, 50.36 parts by weight of silicon monoxide, 30.95 parts by weight of lanthanum titanate, 108.55 parts by weight of holmium oxide, 30.37 parts by weight of praseodymium oxide, 49.58 parts by weight of lutetium oxide, 80.19 parts by weight of cerium oxide and other micron-sized inorganic oxide powder raw materials were mixed uniformly;
[0074] (2) using a high pressure molding machine to mold and granulate the mixed material to obtain a granular material with a particle size ranging from 3 to 5 mm;
[0075] (3) Place the granular material in a vacuum sintering furnace at a vacuum degree of 1.0×10- 2 Pa, sintered at 1400°C for 4 hours to fully react and further improve the density of the pellets;
[0076] (4) vacuum sealing the sintered coating material for future use;
[0077] (5) Place the tempered film substrate (glass) of the mobile phone on a special fixture, and use a cleaning machine and deionized water for ultrasonic cleaning respectively; and use a blower dryer to dry the cleaned substrate at a temperature of 80°C;
[0078] (6) placing the dried substrate on the umbrella stand of the vacuum coating machine and fixing it with a special clamp, and adding the sintered blue light absorbing coating material and silica particles into the crucible;
[0079] (7) Close the hatch, set the deposition rate and film thickness of the coating material and other parameters.
[0080] Run the vacuum coating machine to carry out the vacuum coating process;
[0081] (8) After coating, use a spectrophotometer and a reflectometer to test the product's light transmittance and reflectivity to verify its blue light absorption performance.
[0082] The prepared mobile phone tempered film product covered with blue light absorbing nano-film is brown in color, with an average light transmittance of 65%, a reflectivity of 5%, and a blue light absorption of 55% at a wavelength of 450nm. The product has a higher blue light absorption effect, and the surface reflection is small, soft and not dazzling, meeting the needs of different groups of people.
[0083] Example Data Sheet
[0084]
[0085] Based on the above, it can be known that in the present invention, high-purity micron-grade inorganic raw material powders of different components are mixed evenly by a high-energy ball mill, and then the mixture is granulated by a high-pressure molding machine, and finally the granular material is placed in a vacuum sintering furnace for high-temperature sintering. Under high temperature and oxygen-deficient conditions, oxygen loss and oxygen-snatching reactions occur between the component materials, and finally a dense granular blue light absorbing coating material is formed by sintering. A blue light absorbing nanofilm is formed on the surface of a resin or glass substrate by vacuum coating. The blue light absorbing coating material can adjust the blue light absorption ratio by regulating the proportion of components to meet the needs of different products and different application scenarios, and the product has a low reflectivity, is soft and not dazzling, thereby improving the comfort and experience during use.
[0086] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the term "comprises" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0087] The above description enables those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A blue light absorbing composite rare earth coating material and a preparation method thereof, characterized in that: The steps include: S1: Using a high-energy ball mill, different proportions of micron-sized silicon monoxide, lanthanum titanate, holmium oxide, praseodymium oxide, lutetium oxide, cerium oxide and other inorganic oxide powder raw materials are mixed uniformly; The ratio is: 50.36 parts by weight of silicon monoxide, 30.95 g of lanthanum titanate, 28.55 to 108.55 parts by weight of holmium oxide, 10.37 to 30.37 parts by weight of praseodymium oxide, 9.58 to 49.58 parts by weight of lutetium oxide, and 20.19 to 80.19 parts by weight of cerium oxide; S2: Using a high pressure molding machine to mold and granulate the mixed material to obtain a granular material with a particle size range of 3-5 mm; S3: placing the granular material in a vacuum sintering furnace and sintering it for 4 hours at a vacuum degree of 1.0×10-2Pa and a temperature of 1400°C to fully react and further improve the density of the granular material; S4: vacuum-seal the sintered coating material for future use; S5: placing the substrate on a special fixture, and performing ultrasonic cleaning using a cleaning machine and deionized water respectively; and drying the cleaned substrate using a blower dryer at a temperature of 50°C; S6: placing the dried substrate on the umbrella stand of the vacuum coating machine and fixing it with a special clamp, and adding the sintered blue light absorbing coating material and silica particles into the crucible; S7: close the hatch, set the deposition rate and film thickness of the coating material and other parameters, and run the vacuum coating machine to perform the vacuum coating process; S8: After the coating is completed, use a spectrophotometer and a reflectometer to test the product's light transmittance, reflectivity and other performance to verify the product's blue light absorption performance, and the entire blue light absorption type composite rare earth coating material and its preparation process are completed.
2. A blue light absorbing composite rare earth coating material and a preparation method thereof as claimed in claim 1, characterized in that: In the step S1, the rotation speed of the ball mill is controlled at 300-500 rpm, and the ball milling time is set to 2-4 hours to ensure that the powder raw materials are mixed evenly; at the same time, the ball mill is filled with zirconia balls with a diameter of 3-10 mm, and the ball-to-material ratio is 10:
1.
3. A blue light absorbing composite rare earth coating material and a preparation method thereof as claimed in claim 1, characterized in that: In the step S2, the molding pressure is controlled at 30-50 MPa, and the holding time is 5-10 minutes; the particle size of the granular material is in the range of 3-5 mm.
4. A blue light absorbing composite rare earth coating material and a preparation method thereof as claimed in claim 1, characterized in that: In the step S3, the vacuum degree is maintained at 1.0×10^-2Pa, the sintering temperature is 1400°C, the heating rate is controlled at 5-10°C / min, and the holding time is 4 hours.
5. The blue light absorbing composite rare earth coating material and the preparation method thereof as claimed in claim 1, characterized in that: In step S4, when the product is stored in a vacuum sealed state, a vacuum packaging bag with good sealing performance is used and the product is stored in a room temperature, dry and light-proof environment.
6. The blue light absorbing composite rare earth coating material and the preparation method thereof according to claim 1, characterized in that: In the step S5, during ultrasonic cleaning, the temperature of the cleaning liquid is controlled at 40-60° C., the ultrasonic frequency is 40 kHz, and the cleaning time is 10-15 minutes; the resistivity of the deionized water is greater than 10 MΩ·cm to ensure the cleanliness of the substrate surface.
7. The blue light absorbing composite rare earth coating material and the preparation method thereof as claimed in claim 1, characterized in that: In the step S6, when the substrate on the umbrella stand of the vacuum coating machine is fixed, the distance between the substrate and the coating material is controlled to be 80-120 mm.
8. The blue light absorbing composite rare earth coating material and the preparation method thereof as claimed in claim 1, characterized in that: In step S7, during the vacuum coating process, the deposition rate of the coating material is set to 0.1-0.5 nm / s, and the film thickness is controlled at 50-200 nm according to actual needs; the vacuum degree of the vacuum coating machine is maintained below 1.0×10^-3 Pa.
9. The blue light absorbing composite rare earth coating material and the preparation method thereof as claimed in claim 1, characterized in that: In step S8, when the light transmittance and reflectance are detected, the wavelength range of the spectrophotometer is set to 380-780nm, and the detection angles of the reflectometer are 0°, 45°, and 90°; the blue light absorption performance of the product is evaluated through the detection data.
10. The blue light absorbing composite rare earth coating material and the preparation method thereof according to claim 1, characterized in that: In step S8, after completing the performance test, if the product is qualified, it is packaged, labeled and put into storage; during the packaging process, ensure that there are no scratches or stains on the product surface, and use anti-static and moisture-proof packaging materials; at the same time, the product is batch labeled for easy traceability and management.
Citation Information
Patent Citations
Preparation method of optical radiation protection glasses substrate with high visible light transmittance and substrate
CN116791031A
Medical isolation mask with anti-blue-light and anti-fog effects
CN219108786U
Oxide sintered body and production method therefor, target, and transparent conductive film and transparent conductive substrate obtained by using the same
US20100129660A1
Vapor-deposition material for the production of high-refraction optical coatings
US5340607A